(untitled) (Chemical Engineering Research Bulletin, 2010)
The study presents the e ect of desludging ratio (oil to acid ratio) and adsorption ratio (oil to clay ratio) on the recovery of low pour fuel oil (LPFO) from spent engine oil. Two major unit operations were use to recycle the spent engine oil: the desludging and the adsorption. Concentrated sulfuric acid was used as the reagent to e ect the desludging operation while activated clay was used as the adsorbent in the adsorption operation. The result shows that the efficiency of the recycling operation depends on the reagent ratio used (desludging and adsorption ratios) and increases with the ratios. However, a desludging ratio of 20:1 and an adsorption ratio of 10:1 gave the best recovery of 82.9%. Also the specific gravity, API gravity, pour point, flash point and viscosity index of the recycled oil are lower than the fresh and the spent oil. Keywords: Desludging Ratio, Adsorption Ratio, Low Pour Fuel Oil, Spent Engine Oil, Recovery DOI = 10.3329/cerb.v14i1.4092 Chemical Engineering Research Bulletin 14 (2010) 25-30